Vibrio cholerae hybrid sex factor that contains ampicillin transposon Tn1. - Johnson, S R (1979)
The ampicillin resistance transposon Tn1 was translocated from the R plasmid RP4 to the Vibrio cholerae conjugative plasmid, P. The hybrid sex factor P::Tn1 was highly transmissible and expressed the biological activities of the P factor. In addition, P::Tn1 facilitated transfer of RP4 to V. cholerae recipients. Physical studies of P::Tn1 indicated that the Tn1 transposon was added to the otherwise unaltered P plasmid.